2015
DOI: 10.18203/2320-6012.ijrms20151252
|View full text |Cite
|
Sign up to set email alerts
|

Problems faced by ASHA workers for malarial services under NVBDCP: a cross sectional study

Abstract: Background: About 95% of the country's population resides in malaria endemic areas. The NVBDCP is multifaceted public health programme in the country. The NVBDCP became an integral part of the NRHM launched in 2005. In NRHM, ASHA worker should be placed at grass root level. So role of ASHA is critical at grass root level. Problems faced by ASHA, it will affect the performance. So, ASHA workers positioned at village, Population catered by them, education, work experience, problems related to incentive and any o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…20 A study carried out in Uttar Pradesh revealed that ASHAs cover more population that their estimated population and motivation, incentive and stress level has association with their performance level. 12 The present study also found that 27.3% had population above 1000 and there was a positive association of performance with incentives and difficulty in motivation.…”
Section: Work Environment Factors Influencing the Performance Of Ashassupporting
confidence: 77%
See 1 more Smart Citation
“…20 A study carried out in Uttar Pradesh revealed that ASHAs cover more population that their estimated population and motivation, incentive and stress level has association with their performance level. 12 The present study also found that 27.3% had population above 1000 and there was a positive association of performance with incentives and difficulty in motivation.…”
Section: Work Environment Factors Influencing the Performance Of Ashassupporting
confidence: 77%
“…37.93% ASHAs were having secondary education. 12 Another study done by Choudhury et al also found that 34.02% ASHAs had secondary education. 13 In the existing study, 91% of ASHAs were married and the study done by Das et al also found that 94% of ASHA workers were married.…”
Section: Demographic Profile Of Ashasmentioning
confidence: 93%
“…Malaria control efforts in Odisha were intensified from 2008 onwards, with scaling up coverage of interventions together with active programme management, strong administrative and political commitment as well as substantial state-level financial support. In addition, in 2010 the network of malaria services expanded dramatically with the involvement of village-level female health volunteers, the Accredited Social Health Activists (ASHAs), in the provision of EDCT in malaria endemic areas [4]. Previously, the lowest level of health services was the sub-centre, covering a population of 5,000 people, run by male or female multipurpose health workers.…”
Section: Introductionmentioning
confidence: 99%
“…In various national programs, ASHAs have been well utilized in spreading awareness about diseases like malaria, cancer, diabetes, and hypertension apart from the MCH activities. [ 14 15 ] In a majority of training programs for ASHAs, the knowledge scores were found to increase significantly after training compared to the pre-training scores. [ 16 17 ] It was also noticed that knowledge depleted with time.…”
Section: Discussionmentioning
confidence: 99%